Analisis Efektivitas Program Pengembangan SDM dan Dampaknya terhadap Kualitas Pelayanan Publik di Era Transformasi Digital - Ahmad Yani Kosali; Agung Indriansyah; Sherly Malini; Hatidah Hatidah; M Bambang Purwanto (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The rapid advancement of digital transformation demands that service organizations continuously strengthen their human resource capacity as the cornerstone of competitive service quality. This study analyzes the effectiveness of human resource (HR) development programs and their impact on public service quality at PT Writelab Indonesia, a multi-division service company operating in book printing, clothing/uniform distribution, and non-formal education training. Using a quantitative, descriptive-analytical approach and a survey method, all 20 employees of PT Writelab Indonesia served as respondents via a total sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and analyzed using simple linear regression, t-tests, and the coefficient of determination. Results indicate that the effectiveness of HR development programs was rated Good (mean = 3.56), with training material relevance scoring highest and post-training evaluation scoring lowest. Public service quality was also rated Good (mean = 3.74), with tangibles scoring highest and empathy requiring the most improvement. Hypothesis testing confirmed a positive and significant influence between the two variables, with a t-value of 7.315 > t-table (2.101) and a significance value of 0.000 < 0.05. The R² value of 0.707 indicates that 70.7% of the variation in public service quality is explained by HR development program effectiveness. This study recommends strengthening post-training evaluation systems and integrating digital technology into corporate HR management practices.